2010
DOI: 10.4141/cjas09113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an extended photoperiod in farrowing houses on the performance and behaviour of sows and their litters

Abstract: Lachance, M. P., Laforest, J. P., Devillers, N., Laperrie`re, A. and Farmer, C. 2010. Impact of an extended photoperiod in farrowing houses on the performance and behaviour of sows and their litters. Can. J. Anim. Sci. 90: 311Á319. The effects of an extended photoperiod around parturition and throughout lactation on performances of primiparous sows and their piglets were studied. Sows were assigned to two light regimens: (1) standard (CTL, n 028), 8 h of daily light from day 112 of gestation until day 23 of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It is interesting to note that colostrum and milk content of different cytokines are also regulated by the nocturnal melatonin surge (Pontes et al, 2007). In this study, photoperiod did not alter concentrations of melatonin in blood and milk from sows (Lachance et al, 2010). However, samples were collected after 1000 h, being late after the nocturnal surge of melatonin.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It is interesting to note that colostrum and milk content of different cytokines are also regulated by the nocturnal melatonin surge (Pontes et al, 2007). In this study, photoperiod did not alter concentrations of melatonin in blood and milk from sows (Lachance et al, 2010). However, samples were collected after 1000 h, being late after the nocturnal surge of melatonin.…”
Section: Discussionmentioning
confidence: 60%
“…Farrowings took place from February to July 2008 and photoperiod treatments were equally distributed among each group of farrowing sows each month. Light conditions and quantifi cation of light emissions in each farrowing room and each crate were described previously (Lachance et al, 2010). Briefl y, there was an average of 59 ± 5 lx in front of the crates.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study reported that the duration of time spent standing, laying down, sitting, and kneeling were not affected by light treatment. Lachance et al [20] similarly reported no differences in postural behaviors in sows with an extended photoperiod compared to sows exposed to 8 h of light per day during lactation. Likewise, Simitzis et al [21] reported no postural differences in sows exposed to 8 h of light per day compared to those exposed to 20 h of light per day.…”
Section: Discussionmentioning
confidence: 96%